Association of Platelet Count and Mean Platelet Volume with Overall Survival in Patients with Cirrhosis and Unresectable Hepatocellular Carcinoma - Scheiner, Bernhard (Liver Cancer, 2019)
BACKGROUND: Platelets have been reported to influence tumor biology and may promote metastasis. Traditionally, thrombocytopenia, a hallmark of cirrhosis, was associated with hepatocellular carcinoma (HCC) development. However, the impact of platelet count on outcome in patients with established HCC is not well studied. METHODS: Outcomes of patients with cirrhosis diagnosed with HCC between 1995 and 2013 (derivation cohort) and 2000–2016 (validation cohort) who were not eligible for surgical treatment and did not receive antiplatelet therapy were retrospectively studied. Thrombocytopenia was defined as platelet count < 150 g/L. High mean platelet volume (MPV) was defined as ≥median value of the respective cohort (derivation cohort: ≥11 fL; validation cohort: ≥10.6 fL). RESULTS: Among 626 patients with unresectable HCC, thrombocytopenia was present in 378 (60.4%) and was associated with favorable baseline tumor characteristics: lower diameter of the largest nodule (5.6 ± 3.2 vs. 7.6 ± 4.2 cm), less extrahepatic spread (9.5 vs. 20.2%, both p < 0.001), less macrovascular invasion (21.2 vs. 31.0%, p = 0.005), and lower BCLC stages (63.0 vs. 73.4% BCLC C/D; p = 0.007) as compared to patients with normal platelet count. On univariate analysis, thrombocytopenia and larger MPV were associated with longer overall survival (OS) (thrombocytopenia: median OS [95% CI], 11.5 [9.3–13.8] vs. 5.5 [3.8–7.1] months; p = 0.001; MPV ≥11 fL: 11.7 [9.1–14.2] vs. 6.0 [4.4–7.6] months; p < 0.001). In multivariate analysis, the combined variable of thrombocytopenia and larger MPV was independently associated with longer OS (HR [95% CI], 0.80 [0.65–0.98]; p = 0.029). These results were confirmed in an independent external validation cohort of 525 patients with cirrhosis and HCC. Again, patients with thrombocytopenia and high MPV had significantly longer OS (15.3 [11.7–18.9] vs. 9.3 [7.4–11.2] months; p < 0.001). CONCLUSIONS: Thrombocytopenia and higher MPV are associated with better outcome in patients with advanced HCC. These findings may prompt further clinical research on additive antiplatelet therapy in the prevention and management of HCC.